The Influence Of Price, Location And Promotion On Customer Loyalty Mediated By Customer Satisfaction - Ing Ing; Kandi Sofia S. Dahlan (Ridwan Institute, 2023)
The discussion regarding the role of hotel management towards guests who come to visit to feel satisfied with the services provided and have the desire to visit again at Grand Cordela Hotel Bandung. Hotel management will find ways to attract new prospective customers by providing promotions and events/events so that potential customers are interested and become loyal customers to the Grand Cordela Hotel Bandung. The purpose of this study was to determine and analyze the effect of price, location, and promotion on customer loyalty which is influenced by customer satisfaction, which is at Grand Cordela Hotel Bandung under the operation of Omega Hotel Management - PT Perkasa Internusa Mandiri. The sample of this study used the entire population of guests staying at the Grand Cordela Hotel, Bandung. This research uses correlational quantitative methods and uses Structural Equation Models (SEM). For data processing this research uses the SmartPLS version 4.0 programme. The results of the questionnaire on 34 indicators with a total of 197 respondents were collected after checking and then proceeding with data processing, the results were 5 invalid indicators so the total valid indicators amounted to 29 (twenty-nine) indicators. In this study, there are 10 (ten) hypotheses but after data management, there is 1 (one) hypothesis that is rejected and 9 (nine) other hypotheses are accepted, namely location, promotion, and customer satisfaction have a positive and significant effect on customer loyalty, and price, location, promotion has a positive and significant effect on customer satisfaction and price, location, promotion has a positive and significant effect on customer loyalty mediated by customer satisfaction.